THE EFFECT OF PERSONALITY TYPE AND CLINICAL SUPERVISION TOWARD TEACHERS PERFORMANCE - Raudhatul Husna Chaniago (Jurnal Mantik, 2022)
The purpose of this research was to analyze the effect of personality type and clinical supervision conducted by the principal on teacher performance partially and simultaneously. This research was a quantitative research using a descriptive design. The participants in this study were all civil servant teachers at SMKN 3 Batam during the 2021/2022 academic year. This study's sample size was 50 PNS teachers.  A questionnaire was used to collect data for this study. The selection saturated carried out the technique Technique of sampling. The data was obtained by using a description test instrument and a questionnaire instrument that had been tested for validity and reliability. The results of the research concluded that personality type had a partially significant effect toward teacher performance and clinical supervision had a partially significant effect on teacher performance. Personality type and clinical supervision together affect teacher performance.